Modelling the redistributive impact of indirect taxes in Europe: an application of EUROMOD - Cathal O'Donoghue; Massimo Baldini; Daniela Mantovani (University of Essex, Institute for Social and Economic Research (ISER), 2004)
This paper describes a model to simulate expenditure and indirect taxes in 12 EU countries within the EUROMOD tax-benefit model. The paper outlines the types of indirect taxes in the countries examined. Validation checks are made on the effectiveness of the expenditure models used. The redistributive effect of indirect taxes is decomposed into the tax resulting from different commodity groups. Lastly the progressivity and redistributive effect of indirect taxes are examined and compared with income taxes, social insurance contributions (employee and employer) and the main social benefit groupings with all EU countries.
Keywords: C81; D31; 330; European Union; Microsimulation; Taxation; Redistribution